Extraversion, Scientific Dependency and the Democratisation of Knowledge - AKOLEOWO, Victoria Openif’Oluwa (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Paulin Hountondji is best known for his (in)famous critique of African philosophy as ethnophilosophy. However, while his criticism of African Philosophy has generated much debate, his analysis and critique of extraversion and scientific dependency, the pervading attitude among Global South scholars marked by an intellectual reliance on the Global North academia for relevance and validity have not attracted as much attention. This paper interrogates Hountondji’s critique of extraversion in the light of contemporary global discourse on global epistemic inequalities and the imperative of knowledge democracy. Utilising the qualitative method of research through critical analysis of library texts, it avers that 1) Houtondji’s recognition and acknowledgment of the fact of extraversion and scientific dependency implies a corresponding recognition and acknowledgement of distinct, particular knowledges; 2) his critique of extraversion and scientific dependency necessarilyy implies an acknowledgement of a form of epistemicide/epistemic injustice of/on local knowledge systems. It thereafter, utilising the analytic and synthetic methods of research, argues that Hountondji’s critique places him firmly in the realm of postcolonial scholars who have theorised on the need for the decolonisation and democratisation of knowledge.